Impact of oncoplasty in increasing breast conservation rates Post neo-adjuvant chemotherapy - Koppiker, Chaitanyanand B.; Kelkar, Devaki A.; Kulkarni, Madhura; Kadu, Shweta; Pai, Mugdha; Dhar, Upendra; Deshmukh, Chetan; Varghese, Beenu; Zamre, Vaishali; Jumle, Nutan; Gangurde, Nutan; Joshi, Anjali; et al. (Frontiers in Oncology, 2023)
The essential goal of neo-adjuvant chemotherapy (NACT) is to downstage the primary tumor making it amenable for breast conservation surgery (BCS). However, since the safety of this surgery is paramount, post-NACT breast conservation rates remain low. As per the recommendation of the 2018 Early Breast Cancer Trialists' Collaborative Group (EBCTCG) overview of long-term post NACT follow up we have devised a protocol for imaging, localization, rad-path analysis and documentation of radiotherapy techniques to ensure the safety of post-NACT breast conservation. This is a retrospective cohort of 180 breast cancer patients who received NACT and were operated on by a single surgical oncologist from 2015-2020. After selection based on published guidelines, patients were treated with neo-adjuvant systemic (chemo or hormone) therapy. In cases where primary tumors responded and reduced to 1-2 cm in size mid-NACT, the residual tumors were localized by clips under ultrasound guidance and calcification was wire localized. All patients were treated using appropriate surgical and oncoplastic techniques where indicated. Negative margins were ensured by intraoperative rad-path analysis. Adjuvant chemotherapy and radiotherapy were given as per protocol. In 81 cases that required mastectomy at presentation we were able to achieve a 72.8% post-NACT BCS rate with the help of oncoplasty. Overall, 142 of 180 (80%) patients were treated with breast conserving surgery of which 80% (121 of 142) were oncoplasty. Margins were assessed on intra-operative frozen and re-excised in the same setting. No positive margins were reported in final histopath of 142 breast conservation procedures. Post operative complication rates after breast conservation in the first year were at 17% (24/142 including 2 major complications). Patient Reported Outcomes were satisfactory with increased satisfaction for breast conservation compared to immediate breast reconstruction. Employing oncoplastic breast surgery (OBS) techniques following stringent protocols for accurate localization of the residual tumor, intra-operative rad-path analysis and adjuvant treatments we show successful breast conservation in 72.8% of our mastectomy qualified patients after down-staging by NACT. We also report satisfactory outcomes for post NACT surgery, patient reported satisfaction and survival.